Uncovering determinants and risk factors of pediculosis capitis in boarding school: epidemiological evidence from Pelalawan Regency, Riau Province, Indonesia - Esy Maryanti; Bima Diokta Alparisi; M. Ihsan; Inayah (Berita Kedokteran Masyarakat, 2026)
Purpose: This study aimed to determine the prevalence of pediculosis capitis, analyze its association with risk factors, and apply multiple logistic regression modeling to identify determinant factors and estimate the probability of pediculosis capitis among boarding school students. Methods: An observational, analytic, cross-sectional study was conducted from January to October 2024 at the Boarding School in Pelalawan Regency, Riau Province. A total of 340 junior and senior high school students were recruited using consecutive sampling. Pediculosis capitis was diagnosed through direct examination of the scalp and hair. Data were analyzed using univariate and bivariate analyses, followed by multivariate multiple logistic regression. Results: The prevalence of pediculosis capitis was 31.5%. Bivariate analysis showed significant associations between infestation and gender, hair length, hair shape, sharing personal accessories, and co-sleeping habits (p < 0.05). Multivariate analysis identified female gender (adjusted odds ratio [AOR] = 17.03; 95% CI: 7.07–40.97) and non-straight hair shape (AOR = 2.13; 95% CI: 1.20–3.69) as determinants. The highest estimated probability of infestation was observed among female students with non-straight hair (70%). Conclusion: Pediculosis capitis affected nearly one-third of boarding school students in Riau Province. Female gender and non-straight hair shape were the main determinants, highlighting the need for targeted prevention strategies in high-risk groups.